Analisis Keterkaitan Foreign Direct Investment dan Foreign Portfolio Investment serta Pertumbuhan Ekonomi Tahun 2004 – 2017 - Dona Sandri Simarangkir; Banatul Hayati (Universitas Diponegoro, 2020)
This study aims to analyzing the linkages of growth, foreign direct investment, and foreign portfolio investment with disagregation in term of assets and liabilities with control variable such as inflation, Money Supply, Exchange Rate, and BI Policy Rate. Data used in this study are secondary data, it used from 2004 quarter I until 2017 quarter IV. The result found that there is two-ways causality relationship between Economic Growth and Money Supply. Money Supply has one-way causality relationship on foreign portfolio investment assets, inflation, foreign direct investment with a positive correlation, also exchange rate has one-way causality relationship on JUB with a positive correlation. FDI has one-way correlation relationship with negative correlation on FPIA, inflation, money supply, also Economic Growth has one-way correlation relationship on foreign direct investment. In Variance Decomposition found that fluctuation of Economic Growth are influenced mostly by the shock of Economic Growth itself and followed by foreign directinvestment by 3,33 percent. Thus, the result of the study can be concluded that foreign direct investment are better choice to be focused by the goverment instead of foreign portfolio investment in term to increase the economic growth of Indonesia.